Embodying an Architectural Theory: The Exhibition Yves Klein: Monochrome und Feuer in Mies van der Rohe's Haus Lange, 1961. Issue 1 (2nd January 2019) - de la O Cabrera, Manuel Rodrigo
Abstract: Only one retrospective of Yves Klein was presented during the artist's lifetime, in 1961 at Museum Haus Lange, a gallery in the city of Krefeld, Germany, housed in a little-known brick villa designed by Mies van der Rohe in 1927. The purpose of this article is to demonstrate how Klein challenged the limits of the exhibition, transforming it into a privileged space for the nascent utopian discourse of 1960s European architecture. The exhibition's intense dialogue with the interior and exterior spaces of the Miesian villa afforded an opportunity to test ideas that would have been difficult to accommodate in other circumstances. Klein sought to insert visitors without any notice or warning into a dramatic environment that was the only physical manifestation of his theory of Air Architecture.